Gold‐coating thickness determination on Ag, Cu, Fe, and Pb using a handheld X‐ray instrument. (21st January 2021) - Sabbarese, Carlo; Brocchieri, Jessica; Scialla, Elvira
Abstract : Here, the X‐ray fluorescence technique is used to determine the thickness of a coating layer as well as to analyze the surface of objects. Four metals (Ag, Cu, Fe, Pb) were covered with increasing thicknesses of gold. The measurements were performed with a commercial handheld instrument, X‐SORT (Spectro). In double layers, the thickness of the covering layer was assessed by (a) the ratio between the most intense fluorescence lines of the covered element, (b) a cross‐ratio between two lines of the elements in the two layers, and (c) the ordinary partial least squares (PLS) regression method. In all cases, the curves obtained could be used for the quantitative determination of the thickness. The experimental data followed the theoretical trend even though the values of the attenuation parameters were not always in agreement with the theoretical ones. Comparisons and discussion of the results of the different approaches and also with models in the literature are made. The methods studied were applied to determine the nature of the coating layers of some gilded objects and proved to be suitable for estimating the thickness of gold by providing results that were in good agreement with each other.